PRAZERES, PROFANIAS E EPISTEMOLOGIA SAPATÃO: O feminismo lésbico em Audre Lorde e Monique Wittig - COELHO, Luana Kerly Alves (2026)
This research investigates the constitution of lesbian feminism based on the works of Audre Lorde (2021) and Monique Wittig (2022). The writing assumes personal experience as a political and epistemic method, recognizing the body and experience of the author, a lesbian woman, as a constitutive part of the knowledge production process. The aim is to analyze how the thought of Audre Lorde (2021) and Monique Wittig (2022) contributes to the construction of a lesbian feminism that challenges the cisheterowhite-colonial hegemony of gender and the universal notion of woman. Interdisciplinary in nature, the investigation articulates contributions from literary theory, feminist theory, feminist epistemology, gender studies, and decolonial critiques, understanding that the object of study, lesbianism as a political and epistemological category, cannot be apprehended by a single disciplinary field. Supported by an intersectional and decolonial theoretical framework, this research draws on authors such as Lugones (2010), Gonzalez (2020), and Letícia Nascimento (2023), as well as Wittig (2022) and Lorde (2021) themselves, to challenge the founding myth of feminism and its historical erasures of Black, lesbian, and dissident women. The work adopts a qualitative and bibliographical methodology, with a theoretical-analytical focus, and begins with an analysis of the essays “The Hetero Thinking” (2022) by Monique Wittig and “Sister Outsider” (2021) by Audre Lorde, understood as documents of textual, political, and affective insubordination. By affirming lesbian feminism as an insurgent epistemology, the dissertation proposes the erasure of the CIS-system, the confrontation of the norm, and the opening to a politics of pleasure, writing, and affect as forms of resistance. Ultimately, the text presents itself as a closet door opening, a radical bet on the possibility of thinking, feeling, and existing outside the margins imposed by the norm.